Analysis of Swiftlet Nest Quality In Relation to Price using the Sugeno Method - Lubis, Fitri Handayani; Sitorus, Zunaida (IJISTECH (International Journal of Information System and Technology), 2025)
Many swiftlet nest entrepreneurs in Pangkalan Lunang Village lack a comprehensive understanding of how to assess the quality of swiftlet nests. In fact, nest quality is influenced by various factors, including cultivation techniques, environmental conditions, and post-harvest handling. This lack of knowledge often leads to challenges in maintaining product quality, ultimately affecting selling prices and market competitiveness. Given this situation, it is essential to conduct an in-depth analysis of how nest quality influences its market value. This study employs the Fuzzy Sugeno method to help swiftlet business owners gain a clearer understanding of the relationship between quality parameters—such as color, humidity, shape, and cleanliness—and the selling price. The findings indicate that these quality attributes significantly impact the selling price; the higher the quality, the greater the market value. This emphasizes the importance of adopting best practices in cultivation and post-harvest management to enhance nest quality, meet consumer expectations, and ultimately increase profitability and competitiveness in the market.